2014
DOI: 10.7748/nm2014.02.20.10.22.e1165
|View full text |Cite
|
Sign up to set email alerts
|

Review of non-medical prescribing among acute and community staff

Abstract: All employers of non-medical prescribers (NMPs) have a duty to ensure they remain competent and current, and have access to relevant continuing professional development as identified through their staff appraisals. This article describes a survey that was undertaken to evaluate non-medical prescribing in one trust that operates an acute district hospital and community services. Five themes emerged from the results: prescribing activity, patient safety, effect of non-medical prescribing on care, workforce plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Compliance with therapeutic indications is an important element of pharmacotherapy. International research has shown that the participation of nurses in prescribing improves compliance [26]. Nurse prescribing is most beneficial in the treatment of the elderly (60-85 years old); nurse prescribers also help to reduce polypharmacy in the elderly; and our research also found that nurse supplementary prescribing was predominantly applied in the treatment of elderly patients aged 60-80 years [27].…”
Section: Discussionsupporting
confidence: 60%
“…Compliance with therapeutic indications is an important element of pharmacotherapy. International research has shown that the participation of nurses in prescribing improves compliance [26]. Nurse prescribing is most beneficial in the treatment of the elderly (60-85 years old); nurse prescribers also help to reduce polypharmacy in the elderly; and our research also found that nurse supplementary prescribing was predominantly applied in the treatment of elderly patients aged 60-80 years [27].…”
Section: Discussionsupporting
confidence: 60%
“…Although progress in professional accreditation and regulatory adaptation is recognized, no conclusive studies have been found that thoroughly evaluate the safety of nurse prescribing and patient satisfaction in this context. International studies have shown that nurse prescribing improves treatment adherence [ 44 ]. As in other countries, information on the safety and benefits of nurse prescribing can help guide large-scale implementation and continuity of this practice in Catalonia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this section asked respondents to reflect on all the ESM CPD activities they had completed in the past 12 months and, on a 5-point Likert scale (where participants could indicate that they 'Strongly Agreed', 'Agreed', were 'Neutral', 'Disagreed' or 'Strongly Disagreed') rate their level of agreeance regarding ease of access, affordability, meaningfulness, relevance to scope of practice, improvement in knowledge, and translation to a change in prescribing practice. Questions were developed by the authorship group following a literature review of available relevant CPD surveys [20,[27][28][29][30][31][32] and discussion sessions with ESM podiatrists to ensure the construct was clearly understood. A final open-ended question was presented to participants asking them if they believed improvements could be made to the content, accessibility, relevance, and meaningfulness of CPD for ESM practitioners.…”
Section: Survey Designmentioning
confidence: 99%